Yield-SAFE model improvements. Milestone Report 29 (6.4) - Palma, J.H.N. (2016)
The Yield-SAFE model is a parameter-sparse, process-based dynamic model for predicting resource capture, growth, and production in agroforestry systems that has been frequently used by various research organisations in recent years. Within the AGFORWARD project, the model has been enhanced to more accurately predict the delivery of ecosystem services provided by agroforestry systems relative to forestry and arable systems. This report also summar izes the new developments made in the model which were partially implemented during AGFORWARD modelling workshops held in 1) Monchique in Portugal in May 2015, 2) Kriopigi in Greece in June 2015, 3) Lisbon in Portugal in November 2015 and 4) Lisbon in Febru ary 2016 .